K-Cl Cotransporter 2–mediated Cl− Extrusion Determines Developmental Stage–dependent Impact of Propofol Anesthesia on Dendritic Spines. (May 2017) - Puskarjov, Martin; Fiumelli, Hubert; Briner, Adrian; Bodogan, Timea; Demeter, Kornel; Lacoh, Claudia-Marvine; Mavrovic, Martina; Blaesse, Peter; Kaila, Kai; Vutskits, Laszlo
Abstract : Background: General anesthetics potentiating γ-aminobutyric acid (GABA)–mediated signaling are known to induce a persistent decrement in excitatory synapse number in the cerebral cortex when applied during early postnatal development, while an opposite action is produced at later stages. Here, the authors test the hypothesis that the effect of general anesthetics on synaptogenesis depends upon the efficacy of GABA receptor type A (GABAA )–mediated inhibition controlled by the developmental up-regulation of the potassium-chloride (K-Cl) cotransporter 2 (KCC2). Methods: In utero electroporation of KCC2 was used to prematurely increase the efficacy of (GABAA )–mediated inhibition in layer 2/3 pyramidal neurons in the immature rat somatosensory cortex. Parallel experiments with expression of the inward-rectifier potassium channel Kir2.1 were done to reduce intrinsic neuronal excitability. The effects of these genetic manipulations (n = 3 to 4 animals per experimental group) were evaluated using iontophoretic injection of Lucifer Yellow (n = 8 to 12 cells per animal). The total number of spines analyzed per group ranged between 907 and 3, 371. Results: The authors found a robust effect of the developmental up-regulation of KCC2–mediated Cl − transport on the age-dependent action of propofol on dendritic spines. Premature expression of KCC2, unlike expression of a transport-inactive KCC2 variant, prevented a propofol-induced decrease in spine density. In line with a reduction in neuronal excitability, the above result was qualitatively replicated by overexpression of Kir2.1. Conclusions: The KCC2–dependent developmental increase in the efficacy of GABAA –mediated inhibition is a major determinant of the age-dependent actions of propofol on dendritic spinogenesis. Abstract : The reduction in cortical dendritic spine number induced by propofol sedation of neonatal rats could be prevented by premature expression of potassium chloride cotransporter 2 (KCC2) and the consequent increase in γ-aminobutyric acid–mediated inhibition. The age-dependent reduction in dendritic spine number induced by propofol is controlled by expression of KCC2 that determines γ-aminobutyric acid receptor type A–mediated inhibition, a novel mechanism for anesthetic effects on synaptic plasticity.